Efektivitas Penggunaan Aplikasi Screen Time-Parental Control dalam Penggunaan Gadget Pada Siswa Kelompok B di Ra Raudlatul Mubtadiin - Mukarromah, Lulu; Musayyadah, Musayyadah; Gupita, Norma (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Institut Pesantren Mathali'ul Falah Pati, 2023)
The influence of the use of gadgets in early childhood depends on how parents supervise and direct behavior. Good parenting patterns are needed in accompanying children to use gadgets so that they are in accordance with their functions and avoid the negative impacts they cause. In this study, researchers had the idea to implement the use of the Screen Time-Parental Control application to assist parents in supervising children in using gadgets. The purpose of this study is to find out how the effect of the Parental Control application is in supervising and limiting children who are negatively affected by the use of gadgets, such as gadget addiction and being kept away from negative content that is not appropriate for their age. Data were obtained through questionnaires and in-depth interviews with the parents of RA Raudlatul Mubtadiin students in Toket Village. In this study, researchers used quantitative research methods, with group B students as their research subjects and their parents. The results of the study show that using gadgets for children requires good assistance and care from parents and the application of the Screen Time-Parental Control application can assist parents in supervising children at RA Raudlatul Mubtadiin in using gadgets.